Effects of Buddhist Walking Meditation, Walking Meditation or Mindful Walking on the Health of Adults and Older Adults: A Systematic Review - De Moraes-Ferrari, G (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background: Physical activity is essential for good health and human well-being, yet one-third of adults worldwide fail to achieve the recommended weekly physical activity. Buddhist Walking Meditation (BWM), Walking Meditation (WM), or Mindful Walking (MW) is a mindfulness practice characterized by mind-body interaction, seeking to promote people s well-being. Therefore, this systematic review aimed to examine the effect of Buddhist Walking Meditation, Walking Meditation, or Mindful Walking on health in adults and older adults. Methods: This systematic review (PROSPERO: CRD42024581286) followed PRISMA guidelines. A literature search was conducted in PubMed, SciELO, Web of Science, and Scopus to identify studies that used BWM, WM, or MW as interventions in adults and older adults. The methodological quality was assessed using the PEDro scale, and the risk of bias was evaluated using the Cochrane RoB 2 tool. Results: Ten studies met the inclusion criteria, with intervention durations ranging from 4 to 24 weeks. Most were rated as "good" quality. Positive effects were reported in ankle proprioception, balance, functional fitness, psychological outcomes (e.g., reductions in stress, anxiety, or depression), and selected cardiometabolic markers (HbA1c, blood pressure, and arterial stiffness) in specific subgroups. However, several studies showed a moderate-to-high risk of bias. Conclusions: BWM, WM, and MW are safe and potentially effective PA strategies to enhance physical and mental health in adults and older adults. Their simplicity, low impact, and high adherence rates make them suitable for sedentary or clinically vulnerable populations.